Evaluating Alternative Approaches to GATS Negotiations: Sectoral, Formulae and Other Alternatives - GAO, Henry (Institutional Knowledge at Singapore Management University, 2007)
In addition to the request-offer approach, which is the main approach in the current round of GATS negotiations, the Members have experimented with some alternative approaches over the years. These include negotiations along sectoral and modal lines, as well as those based on certain formulae or quantitative benchmarks. This article will discuss the lessons drawn from the negotiating experiences relating to these alternative approaches, and try to offer some suggestions on how the current and future GATS negotiations could benefit from the use of these approaches.